Students Competence Improvement in Fiction Writing Through Visual Symbol on Language Features Inovation - Nur Antoni Eko Tanuso; Januarius Mujiyanto; Dwi Anggani Linggar Bharati; Hendi Pratama (International Conference on Science, Education, and Technology, 2021)
The study discovered that many students were still puzzled about the use of each tense and word order in writing fiction while teaching "Learning English via Literature." As we all know, fiction differs from the genre works they studied in junior and senior high school; fiction frequently includes metaphorical interpretations in sentences, phrases, or verbs that are foreign to them. The goal of this study is to provide a useful book for students to write fiction using linguistic elements in visual symbols at the English Language and Literature Education Study Program. The precise objectives of this study are to (1) produce a fiction writing technique book based on reader responses to literature, (2) develop an applicable book for writing fiction, and (3) develop an effective book for writing story based on linguistic elements in visual symbols. (1) Self-assessment, (2) expert panels, (3) one-to-one evaluation, and (4) fast prototyping are the research and development methods used. In addition, a requirements assessment is carried out. As a result, the technique of creating fiction employing visual symbol language elements dependent on the reader's response is effective..